Psychopoetry/Poetry Therapy dalam Puisi “Sulaman Rindu” Karya Achmat Nasihi MT - Rini Damayanti; Agung Pranoto (Badan Pengembangan dan Pembinaan Bahasa, 2022)
Psychopoetry is a form of seni-based therapy that psychologists can use for soul-healing. The purpose of this study is to analyse the essay